The Effectiveness of Porpe (Predict, Organize, Rehearse, Practice, and Evaluate) Method to Teach Reading Viewed from Students’ Self-Esteem - Alfan Hadi (LP2M STIT Palapa Nusantara, 2018)
This article reports a study on the implementation of PORPE method to teach reading at the tenth grade students in the academic year of 2012/2013. The objectives of the research are to find out whether: (1) PORPE method is more effective than Direct Instruction Method to teach reading for the tenth grade students; (2) Students who have high self-esteem have better reading skill than those who have low self-esteem; and (3) there is aninteraction between methods of teaching and students’ self-esteem to teach reading. This study was categorized as an experimental research. The population of the research was the tenth grade students in the academic year of 2012/2013. The sample of this research was taken by using cluster random sampling. The sample of this research was 60 students covering 30 students of experimental class taught using PORPE method and 30 students of control class taught using Direct Instruction Method. The data collection was done by giving self-esteem questionnaire and reading test (post-test) after eight meetings of treatment. The data analysis was done by applying descriptive and inferential statistics (ANOVA and Tukey HSD test) to test the research hypothesis. The findings of this research are: (1) PORPE Method is more effective than Direct Instruction Method to teach reading at the tenth grade students; (2) The students having high self-esteem have better reading skill than those having low self-esteem; and (3) there is an interaction between teaching methods and self-esteem in teaching reading. The effect of teaching methods on students’ reading skill depends on the students’ self-esteem level.